As categorias processuais na justiça constitucional limitada - Magano, José Paulo Camargo (2012)
The present work aims to establish the limits of the constitutional protection in the procedural classes in order to assure to that a certification of fair process, dealing, for such purpose, with the morphology of constitutional justice, in which are analysed fundamental institutes of civil procedure, jurisdiction, action, defense and proceedings, under the influence of due process of law, and with the very procedural morphology of the constitutional justice, in which constitutional and procedural disagreements are pointed out, seeking to harmonize them, and finally, making the necessary framework of that protection within the fundamental institutes of process, resulting in a constitutional processualization